Industrialisation in Nigeria : an appraisal - Aliyu, Abdullahi (Lagos, Nigeria : Dilli's Ventures Ltd., 1995)
This book gives a detailed appraisal of industrial development in Nigeria from pre-colonial era to the 1990s.
Includes bibliographical references and index.
jbi 30/04/2018
Loans
Keywords: Industrialization; History; Nigeria